Pergundikan dalam Tangsi Militer Belanda Tahun 1830-1918 - Dilla Sari; Henry Susanto; Yustina Sri Ekwandari (FKIP UNIVERSITAS LAMPUNG, 2019)
The purpose of this study was to determine the process of concubinage in military service, the role of moentji in military service, and the problems caused by concubinage. The method used in this research is historical research method. Researchers use, library techniques, documentation techniques. The data analysis technique used is qualitative data analysis technique. Based on the results of research and discussion, the authors conclude that the recruitment of soldiers carried out in Europe, the Dutch East Indies, and Africa has led to the establishment of concubinage relations that occur in military service. Women who live with European soldiers are called moentji. They were tasked with meeting all kinds of needs of the soldiers in the tank. The concubinage relationship was one of the causes of the spread of venereal disease experienced by the soldiers and this relationship produced children who were mostly abandoned by their parents.Tujuan dalam penelitian ini adalah untuk mengetahui proses munculnya pergundikan dalam Tangsi Militer, peran moentji dalam tangsi militer, dan permasalahan yang ditimbulkan pergundikan tangsi. Metode yang digunakan dalam penelitian ini adalah metode penelitian sejarah. Peneliti menggunakan, teknik kepustakaan, teknik dokumentasi. Teknik analisis data yang digunakan adalah teknik analisis data kualitatif. Berdasarkan hasil penelitian dan pembahasan, penulis mengambil kesimpulan bahwa perekrutan serdadu yang dilakukan di Eropa, Hindia Belanda, serta Afrika telah menyebabkan terjalinnya hubungan pergundikan yang terjadi di dalam tangsi militer. Perempuan-perempuan yang hidup bersama serdadu Eropa disebut moentji. Mereka bertugas memenuhi segala macam kebutuhan para serdadu di dalam tangsi. Hubungan pergundikan turut menjadi salah satu penyebab meluasnya penyakit kelamin yang dialami para serdadu dan hubungan ini menghasilkan anak-anak yang kebanyakan ditelantarkan oleh orang tuanya.Kata kunci: moentji, pergundikan, tangsi militer